2021
DOI: 10.1155/2021/6631963
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Persian Herbal Medicine Compound on the Lipid Profiles of Patients with Dyslipidemia: A Randomized Double-Blind Placebo-Controlled Clinical Trial

Abstract: Introduction. It has been well established in the world that lipid disorders promote the development of atherosclerosis and its clinical consequences. This study aimed to assess the impacts of a Persian medicinal (PM) compound on lipid profile. Materials and Methods. From June 21 to October 21, 2020, a randomized double-blind controlled clinical trial was conducted with 74 dyslipidemic patients, who were randomly divided into two equally populated groups: one prescribed with a Persian medicinal herbal compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…VLDL (p=0.2) and TG (p=0.2) levels also decreased, however not significantly. In conclusion, this study showed that a Persian medicinal herbal compound could be safe and beneficial to decrease the levels of serum cholesterol and LDL in dyslipidemia patients [1].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…VLDL (p=0.2) and TG (p=0.2) levels also decreased, however not significantly. In conclusion, this study showed that a Persian medicinal herbal compound could be safe and beneficial to decrease the levels of serum cholesterol and LDL in dyslipidemia patients [1].…”
Section: Introductionmentioning
confidence: 62%
“…Dyslipidemia is a critical yet controllable risk factor of cardiovascular diseases and causes many deaths globally. Approximately half the popular risk of myocardial infarction and one-quarter of ischemic stroke risk are estimated by elevated LDL and cholesterol levels [1]. In the same study, it was established in the world that lipid disorders promote the development of atherosclerosis and its clinical consequences.…”
Section: Introductionmentioning
confidence: 98%